Optimisation of Goose oil extraction process by response surface methodology - Junli Ning; Mengqing Xiang; Xueli Li; Xinyue Li; Qi Tang; Yan Jiang; Junli Ning (Scientific Reports)
Abstract This study aimed to optimize the ultrasonic-assisted extraction process of goose fat using response surface methodology (RSM) with a four-factor, three-level experimental design to obtain high-quality goose fat that meets national standards. The optimal extraction conditions were determined as follows: ultrasonic power 558 W, extraction time 20 min 36 s, solid-to-liquid ratio 1:5, and temperature 29 °C, achieving an average extraction yield of 78.78%. Verification experiments under these conditions (n = 3) yielded a goose fat recovery rate of 80.22 ± 0.22% (relative error: 0.98%). Scaling up the process by 100-fold (n = 3) resulted in a recovery rate of 81.12 ± 0.22% (relative error: 2.97%). The extracted goose fat exhibited an acid value of 1.112 ± 0.21 mg/g and a peroxide value of 0.031 ± 0.012 g/100 g, both complying with national standards. Accelerated stability tests (60 °C, 24 days) confirmed the fat’s oxidative stability, with acid value remaining below 2.5 mg/g and peroxide value below 0.20 g/100 g. GC-MS analysis identified 23 fatty acids, with unsaturated fatty acids accounting for 59.17% of the total (including 39.94% monounsaturated fatty acids). The optimized extraction process not only ensured high yield but also produced crude goose fat with excellent color and minimal impurities, demonstrating its potential for industrial-scale production.